Tropical pulmonary eosinophilia in a patient undergoing open heart surgery - Shirin, T; Hosain, N; Rasheed, H; Sarker, R; Hassan, R; Chowdhury, AW; Mahmud, R (Mymensingh Medical Journal, 2008)
Mymensingh Med J. 2008 Jan;17(1):98-101. The abstract of this article is available on the PubMed website